PENGARUH METODE SIMULASI TERHADAP HASIL BELAJAR SISWA DALAM PEMBELAJARAN PKN KELAS III SDN 09 - Pania, Heni Evi; Suryani, Suryani; Kresnadi, Hery (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe problem in this research is "Are There Effect Simulation Method Of Learning Outcomes in Learning Civics Class III State Elementary School 09 South East Pontianak?" This study aims to analyze how much influence the implementation of Simulation Method In Learning Citizenship Education Against Student Results class III State Elementary School 09 East Pontianak. This research uses experimental method to form Pre exsperimental design, experimental design with one group pretest-posttest. The population in this study were all students of class III and VI State Elementary School 09 East Pontianak. Data collection techniques used in this study, the measurement technique. Instrument to measure student learning outcomes in the form of an objective test of 35 questions. From the results perhitung effect size (ES) ES obtained amounted to 2,873 (high criteria). This means the application of simulation methods in learning Citizenship Education provides high impact on learning outcomes Elementary School third grade students of 09 countries of Southeast Pontianak.Keywords: Effect, Simulation Methods, Results Learning.